Do changes in maize prices and input prices affect smallholder farmers' soil fertility management decisions? panel survey evidence from Kenya. Issue 2 (3rd April 2022) - Olson, David; Mason, Nicole M.; Kirimi, Lilian; Makau, Joyce
ABSTRACT: Soil fertility management (SFM) practices such as maize-legume intercropping and organic fertiliser, particularly when used jointly with inorganic fertiliser, have the potential to increase yields and yield response to inorganic fertiliser, improve soil health, and contribute to sustainable intensification (SI). However, relatively little is known about the drivers of adoption of these practices, especially for joint use. Moreover, it has been suggested that African farmers will respond to an increase in the maize price they expect to receive at the next harvest by increasing investment in their soils or altering use of SFM practices in response to input price changes. Yet previous studies largely ignore the role of prices. Using nationwide household panel survey data from Kenya, we estimate the effects of changes in crop and input prices on household use of individual SFM practices and combinations thereof. We find that Kenyan smallholders' SFM adoption decisions are largely insensitive to changes in expected maize prices. However, when inorganic fertiliser prices rise, farmers are more likely to use organic fertiliser and use less inorganic fertiliser per acre. These results suggest that price policies alone are unlikely to be effective ways to promote SI of maize production in Kenya.